Development objectives: paper presented at the conference on national reconstruction and development in Nigeria. - Ayida, A. A.; Nigerian Institute of Social and Economic Research (Ibadan : Nigerian Institute of Social and Economic Research, 1969)
This is paper presented at the conference on national reconstruction and development in Nigeria. "Organised by the Federal Ministry of Economic Development, Lagos, and the Nigerian Institute of Social and Economic Research, Ibadan." The paper reviews the industrial progress in Nigeria. It further highlights some of the common produce including their effects and contribution to the national development.
Issued in a case.
asm 06/03/2019
Loans
Keywords: Economic policy; Social conditions; Economic history; Social policy; Nigeria